Synthesis of amorphous silica from sugar cane leaf by chemical extraction method - Nawwar Ayuni, Razali (2012)
Amorphous silica is the chemical compound that also known as silicon dioxide with the chemical formula SiO2. Amorphous silica is the demand raw material nowadays by the chemical industry as it is widely used in the production of resin, optical beads,glass,porcelain and in the semiconductor circuit. Most of the amorphous silica previously were produced from rice husk ash due to its low cost and is environmentally friendly. This research was conducted to find an alternative way and optimum condition to produce amorphous silica from sugar cane leaves ash by chemical extraction method.This is due to its low cost and can be one of the effective ways to dispose agricultural waste.The scope of this research are to study the effect of extraction temperature used during extraction process,the effect of extraction time and the effect of different solvent used to the yield of amorphous silica produced. This research was conducted by using pretreatment method of the sugar cane leaves ash followed by soxhlet extraction method. Based on the results obtained and analysis,it was confirmed that sugar cane leaves is one of the sources to produce amorphous silica and the optimum condition to produce amorphous silica is at high temperature of extraction which is at 80°C,and 8 hours time of extraction and by using methanol as the extraction solvent. The silica obtained from the extraction process was characterized by using Fourier Transform Infrared Spectroscopy (FTIR). As a conclusion, it was confirm that sugar cane leaves contain SiO2 compound based on the wavelength analysis obtained from FT-IR.